Homeostatic Model Assessment for Insulin Resistance Is Associated With Late Miscarriage in Non-Dyslipidemic Women Undergoing Fresh IVF/ICSI Embryo Transfer - Yang, Tianli; Yang, Yuanyuan; Zhang, Qiong; Liu, Donge; Liu, Nenghui; Li, Yumei; Yao, Zhongyuan; Zhang, Yeqing; Tian, Fen; Zhao, Jing; Li, Yanping (Frontiers in Endocrinology, 2022)
Objective: To evaluate the associations between homeostatic model assessment for insulin resistance (HOMA-IR) and pregnancy outcomes in non-dyslipidemic infertile women undergoing in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET). Materials and Methods: This is a retrospective study involving 3615 non-dyslipidemic infertile women, who attend to the Reproductive Medicine Center of Xiangya Hospital, central south university (CSU) between January 2014 and October 2021. Eligible participants were divided into three groups according to the quartiles of HOMA-IR: Group 1 (HOMA-IR <1.46), Group 2 (1.46 to <2.71) and Group 3 (HOMA-IR ≥2.71). Baseline data, clinical characteristics during the assisted reproductive technology (ART) procedure, pregnancy and neonatal outcomes were compared among the three groups. Subgroup analysis based on presence or absence of the polycystic ovary syndrome (PCOS) status was also performed to analyze the effects of HOMA-IR among non-PCOS populations. Results: The late miscarriage rate and percentage of macrosomia increased with the HOMA-IR group (for late miscarriage rate: 2.23% vs. 3.04% vs. 7.35%, P<0.001; for macrosomia: 0.21% vs. 1.70% vs. 3.23%, P=0.002). Increased HOMA-IR (HOMA-IR≥2.71) was positively associated with late miscarriage (crude OR 3.50, 95% CI 1.64-7.47, P=0.001; adjusted OR 3.56, 95% CI 1.56-8.15, P=0.003). In the subgroup analysis, there were 3165 participants in the non-PCOS group and 450 were assigned to the PCOS group. Late miscarriage rate increased with the HOMA-IR group among non-PCOS populations (2.20% vs. 3.03% vs. 7.67%, P<0.001). Late miscarriage rate of PCOS women were comparable among the three HOMA-IR groups (2.50% vs. 3.06% vs. 5.71%, P=0.634). Among non-PCOS women, increased HOMA-IR (HOMA-IR≥2.71) was positively associated with late miscarriage (crude OR 3.71, 95% CI 1.66-8.30, P=0.001; adjusted OR 3.82, 95% CI 1.59-9.17, P=0.003). Conclusions: Late miscarriage rate and prevalence of macrosomia increased with the HOMA-IR index. Preconception HOMA-IR is an independent risk factor for late miscarriage in normolipidemic women undergoing IVF/ICSI-ET. Controlling of insulin resistance before ART might prevent the occurrence of late miscarriage and macrosomia.